Traffic noise at UiTM Shah Alam Campus : initial study / Mohd Muzani Musa, Seti Mariam Ayop and Muhammad Fahmi Md Idris - Musa, Mohd Muzani; Ayop, Seti Mariam; Md Idris, Muhammad Fahmi (2012)
Traffic noise has been identified as a main source of urban noise that generated unhealthy environment in human life. Indeed, the increasing numbers of vehicle totally contributed to the noise pollution around the world. Even though there is standard rules and regulation towards noise limit standard around the world,they still exceed the required limit. Thus, the purpose of this study is to identify the level of noise created by traffic flow in UiTM Shah Alam and also to determine whether the noise level is follows the Department of Environment (D.o.E) Malaysia guidelines or not. The field measurements were carried out to determine Aweighted equivalent continuous sound pressure level LAeq of traffic flow during semester break and academic session. Certain point has been selected to measure the noise level using a sound level meter (SLM). The findings reveal that the overall noise level generated by traffic flow at UiTM Shah Alam was higher than D.o.E requirement which is up to 60 dB.